2016
DOI: 10.1002/app.43965
|View full text |Cite
|
Sign up to set email alerts
|

Development of lignin carbon fibers: Evaluation of the carbonization process

Abstract: The use of lignin as a renewable resource for the production of less-expensive carbon fibers has in recent years attracted great interest. In order to develop the strength properties, the stabilization and carbonization processes have to be optimized. For this reason, the process parameters during carbonization have here been studied on stabilized lignin fibers in the temperature interval from 300 to 1300 8C. The effects of temperature, heating rate, and straining of fibers during carbonization on the strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 29 publications
1
37
0
2
Order By: Relevance
“…By investigating the influence of molecular weight and fusible fractions on the spinnability of softwood lignin-based melt-spun fibers, it was shown that the weight-averaged molecular weight (M w ) should be less than 3,200 Da or the fusible fraction should be ~58.2% to achieve molten lignin for melt spinning [ 100 ]. In most cases of the melt-spun lignin fibers, lignin purification and fractionation, by ultrafiltration [ 96 ], pH-fractionation [ 104 ], and solvent extraction [ 70 , 97 , 105 ], are used to obtain lignin with high thermal mobility and improved performance. Essentially, purification and fractionation [ 106 , 107 , 108 ] can isolate a lower-molecular-weight part (and correspondingly a lower T g ) of lignin for better processability by melt spinning.…”
Section: Mechanical Performance Of Lignin-based Fibersmentioning
confidence: 99%
“…By investigating the influence of molecular weight and fusible fractions on the spinnability of softwood lignin-based melt-spun fibers, it was shown that the weight-averaged molecular weight (M w ) should be less than 3,200 Da or the fusible fraction should be ~58.2% to achieve molten lignin for melt spinning [ 100 ]. In most cases of the melt-spun lignin fibers, lignin purification and fractionation, by ultrafiltration [ 96 ], pH-fractionation [ 104 ], and solvent extraction [ 70 , 97 , 105 ], are used to obtain lignin with high thermal mobility and improved performance. Essentially, purification and fractionation [ 106 , 107 , 108 ] can isolate a lower-molecular-weight part (and correspondingly a lower T g ) of lignin for better processability by melt spinning.…”
Section: Mechanical Performance Of Lignin-based Fibersmentioning
confidence: 99%
“…Kondisi tersebut membuat harga serat karbon menjadi mahal dan waktu pengiriman menjadi lama sehingga dapat mengganggu proses produksi industri pengguna serat karbon. Selain itu, harga serat karbon yang mahal juga sangat dipengaruhi oleh biaya produksinya [7]. Dari seluruh total biaya produksi dalam proses pembuatan serat karbon, biaya terbesar adalah untuk memproduksi atau membeli prekursor serat karbon.…”
Section: Pendahuluanunclassified
“…Although initially lignin-based carbon fibers did not achieve the mechanical properties of traditional carbon fibers, more recent advances in spinning techniques have improved their performance [465]. Electrospinning and melt-spinning are more advantageous fiber processing techniques, but the structure of the lignin, determined by the biomass nature and isolation process, has great influence over the fiber processing [466][467][468]. Under optimized conditions, the properties of the carbon fibers derived from lignin can be similar or even higher than the traditional ones, indicating their good potential for more sustainable engineering applications [469].…”
Section: Lignin-derived Carbon Materialsmentioning
confidence: 99%